Exploring Vocational Fashion Design Programs Through Creative Industry Practices: An Enterpreneurship Perspective - Mahanani, Chytra; Jerusalem, Moh. Adam; Himmah, Laila Nurul; Elvera, Resi Sepsilia; Inayah, Desy Tri (Syntax Literate, 2023)
Changes in the taste of consumer fashion and the development of creative industry technologies have seized wide-ranging opportunities and challenges for the fashion business. Vocational education is based on entrepreneurship that plays a vital role in encouraging innovation steps, the development of skills, and special competencies to form an entrepreneurial mentality, skills and competencies applied in the business world. This research describes a perspective from a point of view of vocational fashion design education in the creative industries business that provides an increasingly prominent picture in the development of the business world. This type of qualitative research used a phenomenological approach in conducting a study of fashion design in the practice of vocational education and creative industries to shape the spirit of entrepreneurship. This research was regarded as an effective data collection involving students of the fashion design department at Universitas Negeri Yogyakarta, Yogyakarta, Indonesia and semi-structured interviews to gather opinions from three main groups of industry professionals, namely fashion designers, creative industries, and specialists. The data was collected from different events, participants’ data, field findings, literacies, coding processes, analysis and representation, criteria for trust and authenticity, and researchers’ reflections within several perspectives. Ultimately, the project methodology was used to create a digital platform, which was proposed as a solution to the research problems. The research findings show several views on how the vocational fashion design education seeks to prepare skills, creativity, competencies, and a number of learners' skills in creative industry practices that provide some opportunities to shape entrepreneurial mentality. The fashion design in the vocational education measures the quality and independent human resources. Other findings prove that promoting the vocational fashion design education paves the way for students to realize their passion and pursue an entrepreneurial success.